The relationship of gadget use to the level of upper trapezius muscle pain with complaints of myofascial pain syndrome - Juliani Saputri; Dadan Prayogo; Wendelinus Imus; Fitri Gunawati (Science Midwifery, 2023)
All fields including education and health are inseparable from the use of technology, one of which is gadgets, besides having benefits for users, there are also many negative impacts from using gadgets, one of which is musculoskeletal disorders. This study aims to determine the relationship between the use of gadgets with the Upper Trapezius muscle with Myofascial Pain Syndrome (MPS) complaints. The design of this study used an analytic observational method with a cross sectional approach. The sample in this study was 12 undergraduate physiotherapy students at the Banjarmasin Human Sanctuary College of Health Sciences who met the inclusive criteria. The results of this study there is a relationship between the use of gadgets with the level of Upper Trapezius muscle pain with MPS complaints by getting a p value <0.05. The conclusion of this study is that excessive use of gadgets will make the neck muscles of the upper trapezius muscles contract continuously which will result in myofascial pain, it is hoped that it can limit the use of gadgets and view for a while to reduce pain in the upper trapezius and stretch.